Layanan Konseling Kelompok untuk Meningkatkan Keterampilan Komunikasi Interpersonal dalam Perspektif Islam - Siti Mauljannah; Hesty Nurrahmi; Amalia Irfani (Pamomong: Journal of Islamic Educational Counseling, 2021)
This study aims to determine the effectiveness of group counseling to overcome interpersonal communication in the Islamic perspective of class XI IPS students at SMA Negeri 1 Sepauk, Sintang Regency. The approach and method used in this research are quantitative approach with the PTBK method. Subjects and locations in research this is a class XI IPS student at SMA Negeri 1 Sepauk, Sintang District have low interpersonal communication in Islamic perspective. Technique data collection used was a questionnaire technique, interview technique, observation technique. The conclusion of this study: 1) gained an overview of communication interpersonal in the Islamic perspective demonstrated by student at the calss XI IPS Negeri Sepauk of Sintang District before the implementation of counseling group. Data results show that group counseling services on students the Ccass XI IPS at SMA Negeri 1 Sepauk of Sintang District is very good, running smoothly so that it can overcome interpersonal communication in an Islamic perspective this can be seen from the results of a post-test cycle I score 86,40% and a cycle II score of 96,93%, from these results indicates that students are experiencing an improvement based on post-test results I and II can thus be said “Ho” rejected and “Ha” accepted.